Wachstumsdeterminanten junger Unternehmen in den alten und neuen Bundesländern: Ein Vergleich zwischen innovativen und nicht-innovativen Unternehmen - Matthias Almus; Dirk Engel; Eric A. Nerlinger (Zentrum für Europäische Wirtschaftsforschung (ZEW), 1999)
The paper deals with growth determinants of innovative and noninnovative start-ups in Eastern and Western Germany. Based on theoretical approaches explaining the growth of firms, hypotheses on potential determinants are derived. The empirical results indicate strong correlations between average annual growth rates on the one side and firm-specific as well as external factors on the other side, influencing growth of start-ups in Eastern and Western Germany in different strength. Higher growth rates can be observed in firms from Western Germany compared with their Eastern German counterparts. Comparing the average growth rates, innovative firms achieve significantly higher rates than noninnovative start-ups in both regions.
Keywords: D92; J23; L11; 330; Innovative Unternehmen; Gründungen; Wachstumsdeterminanten; Unternehmensgründung; Innovation; Unternehmenswachstum; Beschäftigungseffekt; Alte Bundesländer; Neue Bundesländer; Deutschland